Attitude toward sponsorship in Singtel Singapore grand prix : its antecedent and consequence - Lim, Sut Sia (2014)
Sport sponsorship, despite being a lucrative growing market, has encountered challenges and critics in the measurement of its effectiveness. This study intended to build on the study of attitude towards sponsor, an established construct in the field, and purchase intention as the measurement of sponsorship effectiveness. Social identity theory has also been used in the explanation of fan identification, however, it has not been applied to consumer’s identification with an event. Therefore this study sought to find out the applicability of the identification with a sport event in influencing sponsorship outcomes, by introducing it as an antecedent of attitude towards. An online survey was carried out in Nanyang Technological University community and a series of regression tests were done to analyze the data. Results showed that event identification predicted attitude towards sponsor and attitude towards sponsor acted as a partial mediator between event identification and purchase intention. Therefore event identification still has a significant influence on purchase intention. Future studies may consider replicating this in a different type of sports event e.g. mass participation event. Event organizers and sponsors may consider exploring activation plans targeting at increasing both event identification and attitude towards sponsors to maximize the returns on sponsorship investments.